Consultation in a Specialist Mental Health Team for Vulnerable Children before and during the Early Stages of the COVID-19 Pandemic: Audit Findings and Practice-Based Reflections. Issue 2 (3rd March 2022) - Archard, Philip John; Fitzpatrick, Siobhan; Morris, Nicolle; O'Reilly, Michelle
Abstract : In specialist child and adolescent mental health service (CAMHS) provision serving children living in local authority care (i.e. who are looked-after) and other vulnerable groups, consultation with social care professionals and carers is an important part of care delivery. It functions as both a pathway to direct assessment and treatment and an indirect intervention, via formulation, advice and support to the network surrounding a child. This article is concerned with consultation practice in a single multidisciplinary CAMHS team and incorporates two elements. First, it reports on an audit of basic data collected over a 26-month period for quality improvement purposes, and second, it provides practice-based reflections on facilitating consultations during the COVID-19 pandemic. The audit findings, notably that looked-after, adopted, and 13–15 year old children were most likely to be referred on for direct assessment, are discussed and contextualised in a description of local arrangements and working practices, as well as relevant research literature. The reflections involve consideration of changes in problems for which consultations were sought during the initial stages of the pandemic and challenges created by the turn to remote care delivery. In addressing these two tasks, an illustrative example is provided of the role that service audits and practice-based reflection on consultation work can play in helping to identify inequities in access to care in specialist CAMHS teams.